ECG monitoring using Android mobile phone and Bluetooth - De Lucena, Samuel E. [UNESP]; Sampaio, Daniel J.B.S. [UNESP]; Mall, Benjamin; Meyer, Michael; Burkart, Martin A.; Keller, Frieder V. (Institute of Electrical and Electronics Engineers (IEEE), 2015)
This paperwork describes the development and test of circuitry and software to enable the use of Android mobile phones equipped with Bluetooth to receive the incoming electrocardiogram (ECG) signal from a user and show it in real-time on the cell phone screen. The system comprises three distinct subsystems. The first one is dedicated to condition the analog ECG signal, preparing it for conversion to the digital world. The second one consists of a microcontroller and a Bluetooth module. This unit samples the ECG, serializes the samples and transmits them via the Bluetooth module to the Android cell phone. The third subsystem is the cell phone itself. An application program written to the cell phone receives the ECG samples and suitably charts the ECG signal on the screen for analysis. The good quality of the ECG signal allows for identification of arrhythmias.
Keywords: Android; Bluetooth; Cardiac patients; ECG; Embedded systems; Home healtcare; Wireless medical applications